Etiologies and Outcomes of Acute Respiratory Distress Syndrome With No Identified Common Risk Factor. Issue 4 (July 2019) - Gibelin, Aude; Parrot, Antoine; Fartoukh, Muriel; de Prost, Nicolas
Abstract : Almost 10% of patients with acute respiratory distress syndrome (ARDS) have no identified ARDS risk factor at ARDS diagnosis. A prompt identification of the cause of ARDS is required to initiate a targeted treatment. The purpose of this review is to delineate the main rare causes of ARDS and to provide clinicians with a pragmatic diagnostic workup. Recent epidemiological data have proposed the identification of a subgroup of ARDS patients lacking exposure to common risk factors. These can be categorized as having immune-mediated, drug-induced, malignant, and idiopathic diseases. A standardized diagnostic workup including chest imaging, the objective assessment of left-heart–filling pressures, bronchoalveolar lavage fluid microbiological investigations, and cytologic analysis, immunologic tests, and search for pneumotoxic drugs may allow for identifying the cause of ARDS in most cases. Open-lung biopsy should be considered in other cases.